A new species of Hemiodus Müller (Characiformes: Hemiodontidae) from the lower Rio Xingu, Brazil - Da Silveira Silva, Ivanilza; Nogueira, Acácio Freitas; Netto-Ferreira, Andre Luiz; Akama, Alberto; Dutra, Guilherme Moreira (Zootaxa, 2020)
A new species of Hemiodus is described from the Rio Xingu basin, Pará, Brazil. It is distinguished from congeners by the combination of presence of a dark longitudinal stripe extending from head to tip of lower caudal-fin lobe, an oblique blotch on dorsal-fin, 9–11 scale rows above lateral line, 58–66 perforated lateral line scales, and 17–20 circumpeduncular scales. Comments on the conservation status of the new species, as well as its relationships among Hemiodus species, are made.